(untitled) (Journal of the College of Basic Education, 2022)
Man is born and grows in the battlefield of the endless wandering, for he certainly did not make his destiny, and he did not try to paint a picture of the coming tomorrow except through camouflaged and contradictory plans in anticipation of some kind of defeat.So we see him clinging to the contradiction for fear of the unknown and in search of salvation, so the years are shattered, the aspirations die, and the ambition fades, in the blurring of fate and its might, and he stands there without boredom wrestling with life waiting for the coming relief, from the sacred unseen, so he realizes his existence that is associated with faith in the merciful Lord alone...He may not realize it at all, then death and fate surprise him, then we draw his image, but without realizing it at all, because the truth dwells in his heart alone, and he is the only one who possesses it and can reveal its hidden content to the fullness or the light.